Analisis Pengaruhi Health Education Terhadap Peningkatan Pengetahuan, Sikap Dan Perilaku Lansia Pada Kejadian Hipertensi - Latif, Sarifudin Andi; Syafri, Muhammad; Pannyiwi, Rahmat (Jurnal Ilmiah Amanah Akademika, 2022)
Background: Public knowledge regarding hypertension management is currently still lacking. Education is one way that can be used to increase a person's knowledge. Education can be provided in various fields, including health. The aim of the research is to determine the effect of Health Education on increasing the knowledge, attitudes and behavior of the elderly regarding the incidence of hypertension. Method: This type of research is a quantitative research method that uses a pre-experimental study design with pre-test and post-test design treatment. The population is 90 patients suffering from hypertension using total sampling. Results: The results of this study used Wilcoxom test analysis, Knowledge was -8.132 and a significant value of 0.000 (p<0.05), Attitude was -8.165 and a significant value of 0.000 (p<0.05), and Behavior was -8.267 and a significant value of 0.000 (p<0.05), there is a significant difference in the results of the pretest and posttest health education on the attitudes of elderly people with hypertension. These results prove that Ho is rejected and Ha is accepted, which means that there is an influence of health education on the attitude of elderly people with hypertension Conclusion: that there is an influence of health education on the knowledge, attitudes and behavior of elderly people with hypertension.